Advising on the care of the uncircumcised penis: A survey of pediatric urologists in the United States. Issue 6 (December 2018) - Li, Belinda; Shannon, Rachel; Malhotra, Neha R.; Rosoklija, Ilina; Liu, Dennis B.
Summary: Background: Parents of uncircumcised boys often report confusion regarding the proper care and hygiene practices for the uncircumcised penis. The lack of guidance from healthcare providers may be due to a lack of consensus on the proper care of the prepuce. Objective: The aim of this study was to determine whether or not there exists consensus among pediatric urologists on the care of the uncircumcised penis and on the advice they provide to parents. Methods: An electronic survey was delivered to 514 members of the Society for Pediatric Urology (SPU). The survey contained demographical and clinical questions which were analyzed using descriptive statistics. Results: Of 261 SPU members who opened the e-mail invitation, a total of 204 responses were received for a response rate of 78% (overall response rate 40%). Nine responses were excluded for members practicing outside of the United States or whose locations were not disclosed for a final number of responses of 195. Overall, pediatric urologists reported a high level of confidence in providing advice to parents with a median confidence score of 10 (scale 1–10, IQR 9–10). Only 66% reported providing advice to parents on when to begin retracting the foreskin, with 48% basing their advice on the patient's age and 19% on the patient's toilet training status (Figure). Respondents who based their advice on age, advised beginning retraction at 2–5 years (61%), 6–11 years (17%), less than 2 years (12%), and greater than 12 years (10%). For frequency of retraction before toilet training, 50% recommended no retraction, 25% with cleaning or baths, 10% with each diaper change, and 13% provided no advice. After toilet training, 48% of respondents recommended retracting the foreskin with cleaning or baths, 41% with each void, and 19% recommended no retraction. The majority of respondents agreed that problems with voiding (77%), infection (74%), and hygiene (64%) were indications for treatment of phimosis. In asymptomatic cases, 47% believed that phimosis required treatment if persisting beyond a specific age, the most common being greater than 12 years of age (40%). Conclusions: Although pediatric urologists reported being highly confident in advising parents on the care of the uncircumcised penis, there is not a clear consensus among these subspecialists on when to begin and how often to retract the foreskin, or when phimosis requires treatment. These findings offer insight into current practice patterns to better inform primary care providers and parents.Figure. Questionnaire results for factors influencing pediatric urologists' advice on when to begin retracting the foreskin.